Aerodynamic and solid flow properties for flaxseeds for pneumatic separation by using air stream - Amer Eissa, Ayman Hafiz (International Journal of Agricultural and Biological Engineering, 2010)
This study aimed to develop simple empirical equations to predict flaxseeds properties. The first part of the present study deals with the physical, aerodynamic and solid flow properties of flaxseeds which are evaluated as a function of change in moisture content from 8.60% to 23.90% dry basis (d.b.), the dimensions of the length, width and thickness varied from 4.14 to 4.32 mm, 2.03 to 2.13 mm and 0.88 to 0.93 mm, respectively. As the moisture content increased from 8.60% to 23.90% d.b., the bulk density, true density and porosity were found to decrease from 46.65 to 44.89 kg/m3; 1244 to 1176 kg/m3 and 46.65 % to 44.89%, whereas angle of repose and terminal velocity were found to increase from 27.60 to 35.80 and 2.46 to 3.56 m/s, respectively. The static coefficient of friction on various surfaces, namely, plywood, stainless steel, galvanized iron, iron and internal also increased linearly with the increase in moisture content. The results of the experimental investigation may help to optimize some engineering parameters of separation equipment. The second part was carried out on a series of experiments to specify the optimum conditions of separating operation which insure the highest grade of separation efficiency with minimum losses. Pneumatic separation equipment was manufactured and tested under different combinations of the following factors: air stream velocity, feed rate and sample moisture content. The performance of the equipment was evaluated by using the indices separation efficiency and percentage of seed losses. The results of the equipment performances showed that the combinations of air stream velocity, feed rate and sample moisture content affected significantly the separation efficiency and grain losses. Air stream velocity of 2–6 m/s combined with 8.5 kg/h. feed rate and 8.6% moisture content can be considered the most favorable combination values of these variables. They gave the highest grades of separation efficiency and the minimum grain losses. Keywords: flaxseed, physical property, aerodynamics, solid flow properties, pneumatic separation DOI: 10.3965/j.issn.1934-6344.2009.04.031-045 Citation: Ayman Hafiz Amer Eissa. aerodynamic and solid flow properties for flaxseeds for pneumatic separation by using air stream. Int J Agric & Biol Eng, 2009; 2(4): 31<span style="line-height: 140%; font-family: